Pastures of plenty: tracing religio-scapes of prosperity gospel in Africa and beyond - Heuser, Andreas (Studien zur interkulturellen Geschichte des Christentums, 2015)
"Prosperity Gospel, a controversial strand in global Christianity, relates material wealth to divine blessing. Originating in American Pentecostal milieus, it is most successful in Africa. Authors from four continents present interdisciplinary, multi-sited and comparative analyses of Prosperity Gospel in Africa and beyond. Prosperity theologies adapt to varied political contexts and travel outside Pentecostalism into the wider religious arena. Its components trigger discourses within ecumenical Christianity and are transformed in transnational Christian networks of migrants; they turn up in African shrine religion and African Islam. Pastures of Plenty maps the evolving religio-scapes of Prosperity Gospel."--Publisher's summary